2015
DOI: 10.1063/1.4927602
|View full text |Cite
|
Sign up to set email alerts
|

An electrically injected AlGaN nanowire laser operating in the ultraviolet-C band

Abstract: We have investigated the molecular beam epitaxial growth and characterization of nearly defect-free AlGaN nanowire heterostructures grown directly on Si substrate. By exploiting the Anderson localization of light, we have demonstrated electrically injected AlGaN nanowire lasers that can operate at 262.1 nm. The threshold current density is 200 A/cm2 at 77 K. The relatively low threshold current is attributed to the high Q-factor of the random cavity and the three-dimensional quantum confinement offered by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
68
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(69 citation statements)
references
References 32 publications
1
68
0
Order By: Relevance
“…[18][19][20][21][22] Recent studies have shown that spontaneously formed AlGaN nanowire heterostructures with significantly improved optical and electrical properties can be realized via catalyst-free molecular beam epitaxy (MBE). [23][24][25][26][27][28][29][30][34][35][36][37][38] wavelengths of LEDs and lasers using such spontaneously formed AlGaN nanowires have been limited to 250 nm, or longer. 28,35 In the growth process of such spontaneously formed AlGaN nanowires, it involves the use of highly nitrogen rich conditions to promote the formation and nucleation of nanowire structures.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…[18][19][20][21][22] Recent studies have shown that spontaneously formed AlGaN nanowire heterostructures with significantly improved optical and electrical properties can be realized via catalyst-free molecular beam epitaxy (MBE). [23][24][25][26][27][28][29][30][34][35][36][37][38] wavelengths of LEDs and lasers using such spontaneously formed AlGaN nanowires have been limited to 250 nm, or longer. 28,35 In the growth process of such spontaneously formed AlGaN nanowires, it involves the use of highly nitrogen rich conditions to promote the formation and nucleation of nanowire structures.…”
mentioning
confidence: 99%
“…[23][24][25][26][27][28][29][30][34][35][36][37][38] wavelengths of LEDs and lasers using such spontaneously formed AlGaN nanowires have been limited to 250 nm, or longer. 28,35 In the growth process of such spontaneously formed AlGaN nanowires, it involves the use of highly nitrogen rich conditions to promote the formation and nucleation of nanowire structures. However, due to the stronger binding energy of Al-N bond compared to Ga-N bond, 39 this nitrogen rich environment significantly reduces the Al adatom diffusion length, leading to highly nonuniform Al and Ga incorporation, which is evidenced by the commonly observed core-shell structures in AlGaN nanowires, 24,27,30,34,38 and the presence of significant compositional nonuniformity at the nano- 24,25,38,40 and atomic-scale.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…By exploiting the light localization effect in randomly arranged AlGaN nanowires, lasing phenomenon by direct electrical injection has been demonstrated for the first time in the deep UV bands [50,[92][93][94]. The layer-by-layer structure in each individual nanowire is shown in Figure 11a, which consists of the n-GaN contact layer, n-AlGaN cladding layer, AlGaN active region, p-AlGaN cladding layer, and p-GaN contact layer.…”
Section: Electrically-injected Deep Uv Lasersmentioning
confidence: 99%